Clinical and radiographic assessment of mineral trioxide aggregate and calcium hydroxide as apexification agents in traumatized young permanent anterior teeth: A comparative study - S G Damle; Hiteshwar Bhattal; Dhanashree Damle; Abhishek Dhindsa; Ashish Loomba; Sumit Singla (Wolters Kluwer Medknow Publications, 2016)
Background: To evaluate and compare the efficacy of mineral trioxide aggregate (MTA) and traditionally used calcium hydroxide (Ca(OH) 2 ) in inducing root end formation of immature roots of traumatized young permanent anterior teeth. Materials and Methods: The study was carried out on 22 nonvital, immature permanent maxillary incisors. Samples were allotted into two groups - Group I MTA and Group II Ca(OH) 2 Success rate was determined based upon the time duration required for apical barrier formation. The canals were obturated using gutta-percha points in MTA group, after 24 h, whereas in Ca(OH) 2 group, obturation was carried out after radiographic confirmation of the apical barrier. The clinical and radiographic evaluation was carried out at a follow-up periods of 3, 6, and 9 months and statistical analysis was carried out by SPSS version 15.0 statistical analysis software (Chi-square test and fisher exact test). Results: In MTA Group, barrier formation was observed in 90.90% of the patients after 9 months whereas in Ca(OH) 2 Group, the same was observed in 81.81%. The mean time required for barrier formation in MTA group was 4.90 months and 5.33 months in Ca(OH) 2 group. Conclusion: MTA and Ca(OH) 2 , as medicaments for apexification, were comparable in terms of the evaluation parameters. However, MTA was beneficial in terms of immediate obturation of immature roots with wide open apices.